Diferencias en la forma alar de una población colombiana de Anopheles (Nyssorhynchus) nuneztovari Gabaldón, 1940 entre las temporadas seca y lluviosa (2018)
ABSTRACT: The role of Anopheles nuneztovari Gabaldón 1940 as a malaria vector is partially related to its capacity to adapt to diverse environmental conditions. In this context, the anatomy of some structures such as wings, essential for flying, could vary over a short period, as a response to climatic variations. Methods: The wing form (size and shape) of an An. nuneztovari population of Tierralta, Córdoba was compared during the rainy and dry seasons. Twentyone landmarks were digitized on the left wing and wing form was analyzed by geometric morphometrics. Results: There was a significant difference on the average wing size between seasons (p = 0.007), though not on variance (p = 0.85); mosquitoes showed a smaller wing size during the rainy season. Regarding mean wing shape, there was a statistically significant difference between seasons (p < 0.0001), and the correct assignment of the specimens by climate season was 65% for the dry season and 70% for the rainy season. Conclusions: The results suggest a seasonal effect on the wing shape of An. nuneztovari. Further evaluation is recommended to include samples of a larger number of populations for both seasons.